2022
DOI: 10.1101/2022.03.29.486320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-Layered Maps of Neuropil with Segmentation-Guided Contrastive Learning

Abstract: Maps of the nervous system that identify individual cells along with their type, subcellular components, and connectivity have the potential to reveal fundamental organizational principles of neural circuits. Volumetric nanometer-resolution imaging of brain tissue provides the raw data needed to build such maps, but inferring all the relevant cellular and subcellular annotation layers is challenging. Here, we present Segmentation-Guided Contrastive Learning of Representations ("SegCLR"), a self-supervised mach… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 62 publications
2
17
0
Order By: Relevance
“…EM imagery and segmentations, as well as skeletons and cell type tables, are publicly available via https://www.microns-explorer.org/cortical-mm3. All analysis was performed in Python 3.9 using custom code, making extensive use of CAVEclient (https://github.com/seung-lab/CAVEclient) and CloudVolume 112 to interact with data infrastructure, MeshParty 113 to analyze skeletons, and libraries Matplotlib 114 , Numpy 115 , Pandas 116 , Scikit-learn 117 , Scipy 118 , stats-models 111 and VTK 119 for general computation, machine learning and data visualization.…”
Section: Methodsmentioning
confidence: 99%
“…EM imagery and segmentations, as well as skeletons and cell type tables, are publicly available via https://www.microns-explorer.org/cortical-mm3. All analysis was performed in Python 3.9 using custom code, making extensive use of CAVEclient (https://github.com/seung-lab/CAVEclient) and CloudVolume 112 to interact with data infrastructure, MeshParty 113 to analyze skeletons, and libraries Matplotlib 114 , Numpy 115 , Pandas 116 , Scikit-learn 117 , Scipy 118 , stats-models 111 and VTK 119 for general computation, machine learning and data visualization.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to light microscopy, the ultra-high resolution of EM reconstructions provides many additional features that can be used to classify cells by morphology. Previous studies have demonstrated that rich information enabling cell-type classification is available even in local nuclear and peri-somatic features (Elabbady et al, 2022;Al-Thelaya et al, 2021), small segments of neural processes (Dorkenwald et al, 2022c), and the shape of postsynaptic regions (Seshamani et al, 2020). NEURD provides an additional rich and interpretable feature set that can be used for cell-type classification via a number of different approaches.…”
Section: Summary Of Large-scale Dense Em Reconstructionsmentioning
confidence: 99%
“…80 We adapt the above recipe by using the Euclidean distance between NN penultimate hidden-layer representations as a dissimilarity metric, and embed the resulting matrix using UMAP, 67 a general approach not limited to chemistry. 83 Figure 6 shows the resulting structure maps. We use 30,000 atomic environments selected at random from the dataset presented above.…”
Section: Embedding and Visualisationmentioning
confidence: 99%